DIGITAL EMPLOYEE EXPERIENCE, WELLBEING 2.0 DAN KINERJA KARYAWAN PADA ORGANISASI DENGAN SISTEM KERJA HYBRID: STUDI LITERATUR - Maria Helena Carolinda Dua Mea; Ega Leovani (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2026)
Digital transformation and the implementation of hybrid work systems have changed the way organizations manage human resources. Digital Employee Experience (EX) has become a strategic factor affecting employee wellbeing (Wellbeing 2.0) and performance. This study aims to analyze the relationship between digital EX, Wellbeing 2.0, and employee performance through a systematic literature review of scientific publications from 2015 to 2025. The findings indicate that digital EX plays a crucial role in enhancing Wellbeing 2.0 through technology convenience, positive work experiences, and digital support. Wellbeing 2.0 has been shown to act as a mediator that strengthens the impact of EX on performance. This article provides both theoretical and practical contributions for organizations in designing technology-based HR strategies to enhance employee experience and wellbeing.